Penataan Kawasan Kumuh: Studi Kasus Kampung Ledhok Timoho di Bantaran Sungai Gajah Wong - Anisatu Rodiyah; Ellisabet Ambar Eka Sari; Nindya Faristanti; Raphael Arya Hangono; Yusuf Riyan Prasetyo; Rina Jauza Luthfiya; Widya Kusuma Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the issue of slum settlements in Ledhok Timoho Village, located along the banks of the Gajah Wong River in Yogyakarta. The area faces complex social, economic, legal, and environmental challenges, mainly due to the legal uncertainty of Sultan Ground land where many residents live. A descriptive qualitative method with a case study approach was applied. The findings reveal that unclear land ownership hinders residents’ access to public services and decent housing. Local initiatives such as TAABAH have been instrumental in advocating for residents’ rights, yet structural limitations persist. The study recommends implementing long-term residential concession schemes, replicating the livable village model through community participation, revitalizing basic infrastructure, and integrating human rights-based and Sustainable Development Goals (SDGs) approaches. An inclusive and collaborative strategy is essential for slum settlement upgrading that is sustainable, equitable, and respectful of human dignity.